Thermal performance evaluation of continuous khoa cooling system - Shaw, Avijit (Indian Journal of Dairy Science, 2015)
Khoa is an intermediate product widely used as a base material for various indigenous milk sweets. Long duration conventional natural cooling of khoa in open trays not only increases total production time but also results to various browning reactions and microbial contamination. Thermal performance of mechanized khoa cooling system was evaluated to enhance the quality of cooled khoa. The system consisted of an enclosed jacketed tubular screw conveyor. Experiments were conducted at various combinations of 3, 6, 9 screw rotations per minute and 0°, 5°,10° inclination angle of cooling barrel.  Cooling performance was evaluated in terms of overall heat transfer coefficient and cooling efficiency. The residual quantity of khoa left in the system after cooling was also determined. Optimum process parameters for maximum cooling were 9 rpm of screw speed and 10° angle of inclination. The sensory quality of mechanized cooled product was judged by an expert panel. The effect of system operational parameters on sensory attributes of khoa was insignificant.